2011
DOI: 10.1371/journal.pone.0016547
|View full text |Cite
|
Sign up to set email alerts
|

Na+/K+-ATPase α1 Identified as an Abundant Protein in the Blood-Labyrinth Barrier That Plays an Essential Role in the Barrier Integrity

Abstract: BackgroundThe endothelial-blood/tissue barrier is critical for maintaining tissue homeostasis. The ear harbors a unique endothelial-blood/tissue barrier which we term “blood-labyrinth-barrier”. This barrier is critical for maintaining inner ear homeostasis. Disruption of the blood-labyrinth-barrier is closely associated with a number of hearing disorders. Many proteins of the blood-brain-barrier and blood-retinal-barrier have been identified, leading to significant advances in understanding their tissue specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…The major tight junction-associated proteins in the strial capillaries are occludins, claudins, ZOs, and adherens-junction proteins (23,24). The present study found that tight-junction and adhesion proteins were down-regulated substantially in the absence of PVM/Ms.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The major tight junction-associated proteins in the strial capillaries are occludins, claudins, ZOs, and adherens-junction proteins (23,24). The present study found that tight-junction and adhesion proteins were down-regulated substantially in the absence of PVM/Ms.…”
Section: Discussionsupporting
confidence: 55%
“…In an earlier mass spectrometry study, strial capillaries were found rich in tight-junction and cell-adhesion proteins (24). The major tight junction-associated proteins in the strial capillaries are occludins, claudins, ZOs, and adherens-junction proteins (23,24).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The systemic application of glucocorticoids causes side effects such as hyperglycemia and osteoporosis [Cope and Bova, 2008;Trune and Canlon, 2012]. Additionally, the efficacy of systemic glucocorticoid treatment of conditions affecting the inner ear is limited by the low blood flow to the cochlea and the blood-perilymph barrier, which result in low perilymph concentrations of the active compound [Nakashima et al, 2003;Yang et al, 2011]. To minimize side effects and achieve higher perilymph drug concentrations, administration of glucocorticoids directly to the round window membrane via intratympanic injection has been preclinically evaluated and translated into clinical practice [Bird et al, 2011;Chou et DOI: 10.1159/000487662 al., 2013; Han et al, 2015;Shea et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The BLB within the perilymph-filled areas that are part of the blood-perilymph barrier include the cochlear spiral ligament, spiral limbus, modiolus, osseous spiral lamina, vestibular stromal vasculature and the sub-epithelial dark cell area 13 . The vestibular BLB unit in the rodent is similar to the rodent strial BLB unit at the light microscopic level: composed of vascular endothelial cells, pericytes and perivascular-resident macrophage-like melanocytes Recent studies have implicated loss of the integrity of the BLB in several inner ear pathologies including acoustic trauma, autoimmune inner ear disease, and presbycusis 3,7,8,[14][15][16] . Meniere's disease is a disabling syndrome of fluctuating hearing loss, episodic vertigo, and ear fullness, the etiology and pathophysiology of which remain poorly understood.…”
mentioning
confidence: 99%